The genome sequence of Berberis vulgaris L. [version 1; peer review: 2 approved] - Markus Ruhsam (Wellcome Open Research)
We present a genome assembly from an individual Berberis vulgaris (Streptophyta; Magnoliopsida; Ranunculales; Berberidaceae). The genome sequence has a total length of 1,297.50 megabases. Most of the assembly is scaffolded into 14 chromosomal pseudomolecules. The mitochondrial and plastid genome assemblies have lengths of 786.62 kilobases and 166.26 kilobases, respectively.